2019
DOI: 10.1111/1365-2478.12760
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐stack Kirchhoff depth migration local space‐shift imaging condition: synthetic and data examples

Abstract: A B S T R A C TExtracting accurate common image angle gathers from pre-stack depth migrations is important in the generation of any incremental uplift to the amplitude versus angle attributes and seismic inversions that can lead to significant impacts in exploration and development success. The commonly used Kirchhoff migration outputs surface common offset image gathers that require a transformation to angle gathers for amplitude versus angle analysis. The accuracy of this transformation is one of the factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…However, ray-based migrations such as KPSDM tend to be more efficient for large-scale 3D data sets and are favorable for migration velocity analysis in anisotropic media (Liu et al, 2015(Liu et al, , 2018. Other studies have also indicated that KPSDM is a better choice for AVA analysis than more sophisticated migration techniques, such as finite-difference migration or reverse-time migration (Ehinger et al, 1996;O'Brien et al, 2019).…”
mentioning
confidence: 99%
“…However, ray-based migrations such as KPSDM tend to be more efficient for large-scale 3D data sets and are favorable for migration velocity analysis in anisotropic media (Liu et al, 2015(Liu et al, , 2018. Other studies have also indicated that KPSDM is a better choice for AVA analysis than more sophisticated migration techniques, such as finite-difference migration or reverse-time migration (Ehinger et al, 1996;O'Brien et al, 2019).…”
mentioning
confidence: 99%